2022
DOI: 10.1177/20552076221131151
|View full text |Cite
|
Sign up to set email alerts
|

Level of implementation of district health information system 2 at public health facilities in Eastern Ethiopia

Abstract: Objective The major aim of this study was to assess the level of District health information system 2 (DHIS 2) implementation in the public health facilities (HFs) in Dire Dawa City Administration. Methods This study was employed both quantitative (cross-sectional) and qualitative (phenomenological) study designs. All public HFs found in Dire Dawa City Administration and health workers were participated in the study. Quantitative data were collected using a pre-tested, structured, self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…High rates of surgical data inconsistency were a major result of this research and are likely due to lack of consistent KPI reporting forms, and the considerable burden of aggregating substantive data elements into complex indicators as discussed previously by Adane et al 2021 [ 32 ]. Our observations were in alignment with other challenges with data collection in an Ethiopian setting previously discussed including turnover of hospital staff, poor understanding of data processes, modification, or manipulation of data to compensate for the lack of data, and technological issues with DHIS2 [ 28 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…High rates of surgical data inconsistency were a major result of this research and are likely due to lack of consistent KPI reporting forms, and the considerable burden of aggregating substantive data elements into complex indicators as discussed previously by Adane et al 2021 [ 32 ]. Our observations were in alignment with other challenges with data collection in an Ethiopian setting previously discussed including turnover of hospital staff, poor understanding of data processes, modification, or manipulation of data to compensate for the lack of data, and technological issues with DHIS2 [ 28 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
“…al. and other studies [28,30,31]. Our observation of data flow processes demonstrated that SSC values are calculated by QI officers by selecting a sample of ten patient charts for review.…”
Section: Surgical Safety Checklistmentioning
confidence: 53%
See 1 more Smart Citation
“…Our study calculates higher annual surgical volumes for Amhara and Sidama primary hospitals than the 37 per 100,000 found for primary health care units over a 90-day interval. The Amhara primary hospitals showed an overall increase in their surgical volume compared to the previous study during the data intervention in 2018, [30] which may be due to both growth in surgical capacity and population needs.…”
Section: Discussionmentioning
confidence: 98%
“…Decentralisation means that local health administrators need more capacity to analyse and use data for decision-making. Yet the culture of data-sharing and collaborative planning among health stakeholders needs to be enhanced 11 12…”
Section: Introductionmentioning
confidence: 99%